CHARACTERISTICS OF RECURRENCE NASOPHARYNGEAL CARCINOMA IN HASAN SADIKIN HOSPITAL PERIOD 2017-2019 - Adithya Prawiranata, Mohammad; Afriani Dewi, Yussy (TALENTA PUBLISHER, 2020)
Abstract Introduction: Nasopharyngeal carcinoma is a malignancy that occurs in the squamous epithelium in the nasopharynx region. Recurrent Nasopharyngeal carcinoma is defined as tumor recurrence after the complete remission. Patients with recurrent NPC always experience local, regional, or both failure, with or without distant metastases and can damage surrounding tissue.. Methods: This research method was a retrospective descriptive based on medical record data in patients with recurrent nasopharyngeal carcinoma at ORL-HNS outpatient ward subdivision of Head Neck Surgery, RSHS, Bandung from 2017 to 2019. Result: In RSHS Bandung, there was 1727 patient NPC period 2017-2019. There was 135 recurrent nasopharyngeal carcinoma patients (7,8 %) consist of 96 male and 39 female, aged over 40 years as many as 107 patients. More patients were found in T3-T4 (56%), N2-N3(56%), M0 (91%), stage III-IV (75%). The duration of the patient experienced a relapse after initial therapy for more than 24 months (52%). Â Conclusion: Characteristics of recurrent nasopharyngeal carcinoma most of them come with stage III-IV, T3-T4 without distant metastases, with a recurrence within less than 24 months. There was 7,8% recurrent nasopharyngeal carcinoma patients Keywords: Charactherisic, Nasopharyngeal Carcinoma, Recurrence